2011
DOI: 10.1520/jte103132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tensile Strength of Woven Carbon/Epoxy Composite Laminates at Cryogenic Temperatures Using the Open Hole Specimens

Abstract: We propose a combined numerical-experimental method for the evaluation of the tensile strength properties of woven carbon fiber reinforced polymer (CFRP) composite laminates at cryogenic temperatures using the open hole specimens. Cryogenic tensile tests were conducted on the open hole specimens of quasi-isotropic woven CFRP laminates, and the length of the hole edge damage zone corresponding to the specimen failure was determined by the microscopic examinations of failed specimens. A finite element based meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…dog bone instead of rectangular [270]) to those specified by standards, therefore increasing the sensitivity of specimens to boundary conditions such as free-edge effects and clamping [78]. Several authors reported inconsistency in material properties measured at CT in the literature [22,55,124,271], and the deviation from standards is believed to be one reason for this. achieved reduced fixture size by a self-designed jig [273].…”
Section: Manufacturing Methods and Specimen Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…dog bone instead of rectangular [270]) to those specified by standards, therefore increasing the sensitivity of specimens to boundary conditions such as free-edge effects and clamping [78]. Several authors reported inconsistency in material properties measured at CT in the literature [22,55,124,271], and the deviation from standards is believed to be one reason for this. achieved reduced fixture size by a self-designed jig [273].…”
Section: Manufacturing Methods and Specimen Configurationmentioning
confidence: 99%
“…1b) is shattered into several chunks due to its ductility and subsequent redistribution of load after local fibre failures. Poisson's ratio should become lower with decreasing temperature due to the increased stiffness of the resin [70], but several authors reported increased values at CT [45,55,59,60]. A possible explanation can be the difference in increase in longitudinal (𝐸 1 ) and transverse (𝐸 2 ) elastic modulus.…”
Section: Tensionmentioning
confidence: 99%
See 1 more Smart Citation